Uji Efektivitas GELL Obat Jerawat Dari Ekstrak Etanol Buah Pare (Momordica charantia L.) Terhadap Pertumbuhan Bakteri Propionibacterium acnes - herviani sari; Firdaus Fahdi (Jurnal Penelitian Farmasi & Herbal, 2020)
Bacterial infection is a major factor in causing acne. The causes of acne are many (multifactorial), including genetic, endocrine, dietary factors, the activity of the sebaceous glands themselves, psychological factors, mucin, infection by Propionibacterium acne, cosmetics, and other chemicals. Pare extract can be formulated as a gell pimple, which can inhibit the growth of propionibacterium acne. The samples in this study were gell preparations of the ethanol extract of bitter melon with a concentration of 5%, 7.5%, 10%. Based on the results obtained, the addition of the ethanol extract concentration of bitter melon fruit depends on the extract produced. The higher the concentration of gell preparations, the better it is to inhibit bacterial growth. The results showing that pare fruit extract with a concetration of 5%, 7,5%, 10%, and as gell verile 0,025% get a variety of results. And a good resistance zone on the three concentrations that are most close to verile effectiveness is 10% concentration. In conclusion, bitter melon extract can be formulated as an acne medication that can inhibit the growth of the Propionibacterium acnes bacteria.